PENGARUH PROMOSI KESEHATAN DENGAN METODE CERAMAH TENTANG KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG SEKS PRANIKAH - novia artika; Riska Ratnawati (Dian Nuswantoro Semarang, 2020)
Reproductive health is a healthy condition with reproductive systems, functions, and processes possessed by adolescents. Lack of knowledge and attitudes about reproductive health affect premarital sexual behavior. One effort to increase knowledge about premarital sex is to provide health promotion. This study aims to determine the effect of health promotion with the lecture method on reproductive health to the knowledge and attitudes of adolescents about premarital sex in